Puasa Ramadlan dalam Kajian Kitab Nihayatuz Zain (Analisis dari Persepektif Fiqih, Tasawuf dan Kesehatan) - Aminah , Siti; Musthofa, R. Zainul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The Book of Nihayatuz Zain is one of the books by Indonesian scholars, namely scholars who have recognized their knowledge and wisdom as well as their expertise in the field of science, especially religious sciences. His expertise and expertise in science are not only recognized and recognized in the national or domestic scope, but also have reached overseas or international scope. He is Sheikh Imam Nawawi al Bantani. The Book of Nihayatuz Zain is a book of Fiqh based on the As-Syafi'i school, which is quite well known in Indonesia. This book is a syarah from the book